Manajemen Publik dalam Transformasi Ekonomi Digital Sentra Wisata Kuliner di Surabaya - Alvi Nazwa Rindiana; Nailah Talitha Salsabila; Nayif Achamd Fannur; Anisa Qorina Safitri; Meirinawati Meirinawati; Trenda Aktiva Oktariyanda (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the effectiveness of public management in navigating the digital economic transformation at the Culinary Tourism Centers (SWK) in Surabaya through the POSC theory approach. The research employs a qualitative descriptive method with a literature study design, evaluating various policy documents, government publications, and scientific articles related to the implementation of the E-PEKEN platform and the QRIS payment system. The findings indicate that digital strategy planning has been integrated with the 2025-2029 Surabaya Regional Medium-Term Development Plan (RPJMD) vision, although physical infrastructure synchronization at several locations remains a challenge. Organizing is conducted in a cross-sectoral collaborative manner involving academics through a strategic partnership model. Regarding the staffing aspect, personal technical assistance provided by field staff and students has proven crucial in increasing traders' digital literacy, as evidenced by the significant improvement in understanding at the Wonorejo SWK unit, which rose from 56% to 89%. The controlling mechanism is carried out through digital transaction monitoring, although technical network stability remains the primary obstacle to program sustainability. The novelty of this research lies in the systematic application of classical management theory to dissect the dynamics of the informal sector during the digital transition at the local level. These implications emphasize that the success of MSME digitalization depends not only on technology but also on sustainable human resource mentoring. This study contributes to advancing knowledge in the field of organizational management psychology, specifically regarding technological adaptation behavior among micro-entrepreneurs within the public bureaucracy environment.